TRANSFORMING ENERGY POLICY IN INDONESIA: ADDRESSING GENDER BIAS AND PROMOTING WOMEN’S EMPOWERMENT IN THE RENEWABLE ENERGY SECTOR - Adventi Ferawati Sembiring; Evis Garunja (Jurnal Hukum Progresif, 2026)
This study analyses the role and engagement of women in Indonesia’s renewable energy transition through a feminist perspective, emphasising the shift from gender-neutral frameworks to inclusive, equitable, and justice-oriented approaches. The research employs document analysis of national energy plans, with a focus on the “Sumba Iconic Island” programme as a case study, complemented by a literature review that addresses ethics of care, distributive justice (Gilligan, Noddings, Rawls), and feminist perspectives—specifically standpoint theory and intersectionality. It highlights the patriarchal biases embedded in technocratic and macroeconomic policy frameworks. Although Indonesia possesses a wealth of renewable resources—including solar, bioenergy, and ocean waves—women’s experiential knowledge and perspectives remain underrepresented in energy policy and planning. Existing evidence indicates that empowering women as technicians and energy educators enhances technology adoption, social effectiveness, and long-term sustainability. A comparative analysis of Iceland and Germany shows that mandatory gender-equity reporting and inclusive public consultations—guided by feminist perspectives—position women as strategic partners in energy decision-making, rather than passive beneficiaries. Proposed actions include the adoption of feminist-informed Gender Responsive Budgeting (GRB) in energy-sector funding, revising technical regulations to require assessments of gender-power impacts, and establishing women’s energy advisory forums at both national and regional levels. These measures aim to reshape Indonesia’s energy transition into a process that is equitable, inclusive, fundamentally feminist, and environmentally sustainable.